Emerging agents for the treatment of metastatic urothelial cancer - Whi-An Kwon; Ho Kyung Seo (Investigative and Clinical Urology, 2021)
Over the past few decades, platinum-based combination chemotherapy (PBCC) has been the preferred initial therapy for metastatic urothelial cancer (mUC). However, despite a response rate of approximately 50%, a small proportion of patients with distant metastases may be cured by cisplatin-based combination chemotherapy (CBCC). In addition, up to 50% of patients are not eligible for CBCC due to age or comorbidities. Furthermore, adverse effects from PBCC are a major concern. The emergence of check-point inhibitors (CPIs), particularly those with antibodies directed against programmed cell death 1 protein (PD-1) or its ligand (PD-L1), advanced the treatment of mUC. Avelumab switch-maintenance therapy is recommended in patients with locally advanced or mUC who did not progress on initial PBCC. With the recent advances in tumor molecular biology and the discovery of actionable therapeutic targets, the clinical application of targeted therapy is now being explored for mUC. Erdafitinib, a tyrosine kinase inhibitor of FGFR1–4, has shown positive outcomes in patients with advanced UC with FGFR alterations. Another recent technological development is antibody-drug conjugates (ADCs), which are complex molecules composed of an antibody linked to a biologically active cytotoxic drug (payload) that targets and kills tumor cells while sparing healthy cells. Enfortumab vedotin, a monoclonal antibody targeting nectin-4 conjugated to monomethyl auristatin E, has demonstrated clinically significant efficacy in patients who do not respond to both cytotoxic chemotherapy and CPIs. In this review, we describe switch-maintenance therapies using CPI, various targeted agents, and ADCs that have been investigated for mUC treatment.